The palm kernel oil ester nanoemulsion system using pluronic F-127 as a polymeric surfactant via a high energy emulsification method - Zahari, Noor Izah; Basri, Mahiran; Basri, Hamidon; Abdul Malek, Emilia; Karjiban, Roghayeh Abedi (Malaysian Palm Oil Board, 2014)
The study of formation of nanoemulsions by low energy emulsification method was carried out in water/surfactant/oil system. Palm kernel oil ester (PKOE) was used as the oil phase while Pluronic F-127 was chosen as the surfactant. A ternary phase diagram was constructed for the water/Pluronic F-127/PKOE system by changing the composition concentration at constant temperature. The pre-emulsions were prepared based on the constructed phase diagram via a low energy emulsification and these were characterised with respect to centrifugation force and particle size. Since the particle size formed was large, they were then subjected to high energy emulsification to reduce the particle to nano-size. Formulations with particle size from 93-127 nm were successfully formed. Kinetic stability was assessed by measuring particle size as a function of time and storage condition. Droplet size of the formulations did not show any significant changes with 135 nm after three months. The morphology study was carried out on two formulations using low energy and high energy emulsification. Formulation using high energy emulsification showed an image with smaller and well distributed droplets compared to low energy emulsification.